SUB-ANTARCTIC GARDENS: KNOWLEDGE AND APPRECIATION OF HIGH ANDES FLORA - Mendez, Manuela O.; Cavieres, Lohengrin; Rozzi Marin, Ricardo Roberto (My University, 2018)
This work proposes a new concept for changing the perception about the high mountain habitats in the sub-Antarctic region of Cape Horn, from a "high-Andean desert" toward gardens where positive ecological interactions thrive. We generate this change through a practice of field environmental philosophy that involved the composition of metaphors and the design of field activities guided with an ecological and ethical orientation. This new concept aims to refine the observation and understanding about the life habits of mountain's plants, where cooperation enhances the richness of species that con-inhabit in these high-Andean habitats. We demonstrated that cushion life-habit prevails in these environments, among both vascular and non-vascular plants. To foster an ethical valuation and a synthesis of the ecological discoveries about these life habits and the positive interactions they establish with other species, we composed the metaphor: "High-Andean sub-Antarctic gardens."
Keywords: biocultural ethics; conservation; metaphors; interspecific cooperation